Oczyma wyobraźni – o znaczeniu zabawy w rozwoju dzieci niewidomych - Lewandowska, Patrycja; Jakoniuk-Diallo, Anna (Studia Edukacyjne, 2022)
The Article points to the meaning of children’s play time, in the stimulation of development in blind People. The authors highlight the role of specialized types of play, i.e. didactical and rehabilitation, in the process of supporting early development.